The Effectiveness of Computational Thinking Based Learning (CTBL) and Problem Based Learning (PBL) Learning Models on Learning Achievements Reviewed From Brain Dominance - Swasti Maharani; Toto Nusantara; Abdur Rahman As’ari; Abd.Qohar (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aimed to determine: (1) which one is more effective between Computational Thinking BasedLearning (CTBL) and Problem Based Learning (PBL) on learning achievement, (2) which one is better,students with left brain dominance or students with right brain dominance, (3) for each brain dominance,which one is better between CTBL and PBL. This study used a quasi-experimental research method witha 2x2 factorial design. The population in this study were all students of class VIII SMPN 1 Bendo in theAcademic Year 2020/2021, totaling 9 classes. The research sample included 45 students (two classes) whowere taken using cluster random sampling. The instrument used was a questionnaire on the students’ braindominance and a mathematics learning outcome test. From the results of this analysis, it can be concludedthat CTBL was more effective to implement compared to PBL in odd semester class eight students at SMP1 Bendo Magetan in the Academic Year 2020/2021. There were differences in the results of mathematicslearning achievement in students who were given CTBL and PBL in terms of the brain dominance of oddsemester class eight students at SMPN 1 Bendo Magetan in the Academic Year 2020/2021.